2002
DOI: 10.1016/s0885-3924(01)00367-0
|View full text |Cite
|
Sign up to set email alerts
|

Nebulized Furosemide as a Novel Treatment for Dyspnea in Terminal Cancer Patients

Abstract: Three terminal cancer patients with severe dyspnea were treated with nebulized furosemide. The underlying causes of dyspnea varied. Twenty milligrams of furosemide was nebulized and inhaled four times each day. Dyspnea dramatically improved and could be controlled for weeks. No noticeable side effects were observed. Inhalation of nebulized furosemide seems to be an effective and useful treatment for dyspnea in terminal cancer patients, but these observations need to be confirmed in a randomized controlled tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 13 publications
2
29
0
2
Order By: Relevance
“…Studies performed using inhaled furosemide have been small and uncontrolled, but results have been positive. [13,14] Wilcock et al (2008) conducted a randomized controlled study and reported that nebulized furosemide had no impact on dyspnea with cancer patients and did not cause any side effects. [15] Despite participants stating that they felt relief from the dyspnea, there were no statistically significant results in another randomized controlled trial examining the effect of nebulized furosemide in the management of cancer-related dyspnea.…”
Section: Diureticsmentioning
confidence: 99%
“…Studies performed using inhaled furosemide have been small and uncontrolled, but results have been positive. [13,14] Wilcock et al (2008) conducted a randomized controlled study and reported that nebulized furosemide had no impact on dyspnea with cancer patients and did not cause any side effects. [15] Despite participants stating that they felt relief from the dyspnea, there were no statistically significant results in another randomized controlled trial examining the effect of nebulized furosemide in the management of cancer-related dyspnea.…”
Section: Diureticsmentioning
confidence: 99%
“…This finding led to inhaled furosemide being evaluated in cancer patients. A group of three cancer patients reported improved dyspnea when given nebulised furosemide (20 mg) (Shimoyama et al, 2002). Nebulisation of a bronchodilator before giving inhaled furosemide had no effect and the authors excluded a placebo effect.…”
Section: Furosemidementioning
confidence: 99%
“…In an uncontrolled study in patients with endstage cancer, Shimoyama and Shimoyama [ 55 ] reported on three patients whose dyspnea, refractory to opioids, dramatically improved for weeks with 20 mg of inhaled furosemide four times a day, with individual treatment effects lasting for up to 4 hours. In controlled experimental settings with volunteers, furosemide decreased dyspnea generated by breathholding, hypercapnia, and hypercapnia together with increased work of breathing [ 56 , 57 , 58• ].…”
Section: Inhaled Furosemidementioning
confidence: 99%